Exploring the Eastward Transmission of Augustine’s Confessions in Mainland China: A Comprehensive Analysis - Zhou, Weichi (Religions, 2025)
During the late Qing Dynasty and the Republican China period, Augustine’s book, Confessions, had been translated into Chinese. Out of the six Chinese versions of the book available, the one published by the Commercial Press in 1963, translated by Mr. Zhou Shiliang 周士良, is the most widely used version in mainland China. It is worth noting that this version was preceded by five other Chinese translations. This paper provides a detailed analysis of the translation of Augustine’s Confessions in mainland China. This study examines the distinct features of the Chinese versions during the late Qing Dynasty and the Republic of China period. Additionally, this article explores the transmission of the translated book title, Chanhui Lu 懺悔錄 (Confessions), and the discussions surrounding its precise meaning and translation during the Republic of China period. Ultimately, this study sheds light on the eastward transmission of Augustine’s Confessions in mainland China.